The Quality of Relationship with Stakeholders, Performance Risk and Competitive Advantage in the Hotel, Restaurant and Café Market - Skudiene, Vida; McCorkle, Yuhua; McCorkle, Denny; Blagoveščenskij, Daniil (Organizations and Markets in Emerging Economies, 2021)
While emerging markets have become an opportunity for companies in the less populated and saturated markets to expand their business, they also impose challenges for foreign partners’ competitive behavior. To offer the value that would be competitive in emerging markets, companies need to improve the quality of their relationship with business partners. Relationship quality may enhance the probability of continued interchange between companies and their stakeholders, leading to increased attractiveness for the emerging markets’ economy. This research explores antecedents (communication and relationship longevity) of relationship quality with stakeholders (suppliers, customers, and employees) and how the relationship quality with three stakeholders impacts the company’s performance risk and competitive advantage in the Lithuanian hotel, restaurant, and café market. The findings suggest that communication and relationship longevity have a positive effect on relationship quality with all three stakeholders. A higher level of relationship quality with stakeholders has a more positive effect on competitive advantage and a more significant negative effect on performance risk. The study expands the understanding of relationship quality antecedents (communication and relationship longevity) and relationship quality with customers, suppliers, and employees in terms of competitive advantage and performance risk in the less populated and saturated hotel, restaurant, and café market seeking expansion to emerging markets.
Keywords: relationship quality; performance risk; competitive advantage; hotelrestaurant, and café market; a developed country with low population